Commanding Right And Forbidding Wrong: A Behavioral Investigation Using The Rowing Game - Hazik Mohamed (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2019)
There have been many empirical investigationinto property rights and rule of law in economic development, they do not demonstrate how deep religious understanding in human behavior for mutually beneficial decision-making. This paper attempts to address this concern so as to understand religious beliefs in constructive actions. This paper investigates the degree of compliance of individual behavior to the Islamic commandment of 'commanding right and forbidding wrong', through a behavioral approach, to understand the pervasiveness of Islamic morality in our modern societies, and how Muslims actually behave as opposed to what the Qur'an prescribes for them. The methodology of this researchevaluates the actions of experiment participants (divided into religious affiliations) through a Rowing Game that was intended to test for the rule of 'commanding right and forbidding wrong'. “The game is a prototype of a social contract where it illustrates how 'mutual undertakings' create a psychological tension between individual rationality, group benefit and straightforward compliance to Allah's commandment” (Mohamed et al, 2018). The complex nature of this command and prohibition results from the varied understanding of who is responsible (and adept enough) to enforce it, during which time is appropriate to do so and by what means. In this particular experiment, Muslims and non-Muslims appear to perform the same, with negative priming effects on the Muslims and positive priming effects for the non-Muslims.